Pembelajaran Bahasa Arab di Pesantren Sultan Hasanuddin Limbung Gowa - Fauziah Bachtiar; Muhammad Radhi Al Mardhi; Muh. Bachtiar Syamsuddin (Peneliti.net, 2023)
Islamic Boarding School is one of the best means of learning foreign languages, especially Arabic. With an effective and conducive environment, Arabic learning can be carried out effectively and productively, because the students not only get material about the Arabic language, but can practice it directly in their daily lives. Pesantren Sultan Hasanuddin Limbung Gowa has implemented this in the process of learning Arabic for its students and students. This research is a type of qualitative research conducted by collecting data then analyzing and drawing conclusions by describing the results of the research. The results and conclusions of this study are to obtain a complete understanding and information about the process of learning Arabic at the Sultan Hasanuddin Islamic Boarding School which is compiled using a pesantren-based Madrasa curriculum so that all activities carried out formally and non-formally, can create a language environment or al-bi. 'ah al-lughowiyah is formed effectively and is able to cover the four Arabic language skills, speaking (maharotul kalam), listening (maharotul istima'), reading (maharotul qiro'ah) and writing (maharotul kitabah) as well as making students able to communicate. and productive and confident in communicating using good and correct Arabic.